1993
DOI: 10.1128/jb.175.6.1823-1830.1993
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetics of sulfur reduction in the hyperthermophilic archaeon Pyrococcus furiosus

Abstract: The bioenergetic role of the reduction of elemental sulfur (SO) in the hyperthermophilic archaeon (formerly archaebacterium) Pyrococcusfuriosus was investigated with chemostat cultures with maltose as the limiting carbon source. The maximal yield coefficient was 99.8 g (dry weight) of cells (cdw) per mol of maltose in the presence of So but only 51.3 g (cdw) per mol of maltose if So was omitted. However, the corresponding maintenance coefficients were not found to be significantly different. The primary ferme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
78
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 55 publications
4
78
0
Order By: Relevance
“…On the other hand, some of these organisms, such as P. furiosus, are able to grow in the absence of S0 by fermentation and produce H2. In these cases, So reduction was originally thought to be a mechanism of detoxifying inhibitory H2 (18 (42). Moreover, on the basis of the unusual ferredoxin-dependent "pyrosaccharolytic" pathway that P. furiosus is proposed to use for carbohydrate fermentation, it was calculated that So reduction is equivalent to an ATP yield of 0.5 mol of ATP per mol of S0 reduced (42).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, some of these organisms, such as P. furiosus, are able to grow in the absence of S0 by fermentation and produce H2. In these cases, So reduction was originally thought to be a mechanism of detoxifying inhibitory H2 (18 (42). Moreover, on the basis of the unusual ferredoxin-dependent "pyrosaccharolytic" pathway that P. furiosus is proposed to use for carbohydrate fermentation, it was calculated that So reduction is equivalent to an ATP yield of 0.5 mol of ATP per mol of S0 reduced (42).…”
Section: Resultsmentioning
confidence: 99%
“…In these cases, So reduction was originally thought to be a mechanism of detoxifying inhibitory H2 (18 (42). Moreover, on the basis of the unusual ferredoxin-dependent "pyrosaccharolytic" pathway that P. furiosus is proposed to use for carbohydrate fermentation, it was calculated that So reduction is equivalent to an ATP yield of 0.5 mol of ATP per mol of S0 reduced (42). It was therefore of some surprise to find that the sulfhydrogenase (sulfur:reduced ferredoxin oxidoreductase) activity of P. furiosus was located in the cytoplasm (26).…”
Section: Resultsmentioning
confidence: 99%
“…furiosus also reduces elemental sulfur (S 0 ) to H 2 S. This process decreases the amount of H 2 produced and has a stimulatory effect on growth, as indicated by an increase in cell density and growth rate (11). Moreover, during growth on maltose, the cell yield per gram of substrate used is 50% higher if S 0 is present in the medium (35). This suggests that the reduction of S 0 by P. furiosus is not merely a means of disposing of excess reductant but rather is an energy-conserving process.…”
mentioning
confidence: 99%
“…These have fermentative-type metabolisms and produce H 2 during growth, although they also produce H 2 S if S 0 is added to the growth medium. S 0 reduction was thought to be a mechanism of detoxifying inhibitory H 2 (23), but a more recent study showed that H 2 S production plays a role in energy conservation by an as yet unknown mechanism (62). The best studied of the hyperthermophiles that are not obligately S 0 dependent is Pyrococcus furiosus, which grows optimally at 100ЊC (23).…”
mentioning
confidence: 99%